Innovation and quality processes in software development of Smes, in Baja California, Mexico - Carlos Valdés Hernández, Roberto; Luis Arcos Vega, José; Fernando González Navarro, Félix (International Journal of Engineering and Technology, 2019)
The objective of this article is to research the impact that innovation has in the development and quality of software production processes, and in turn, how innovation influences the profitability of small- and medium-sized enterprises (SMEs). This research was carried out with a sample of 52 enterprises in the software area in Baja California, Mexico. The collection of data was made from June to September 2016, with the support of a survey aimed to the enterprisesâ€™ managers. For the analysis of the model and validation of structured relations, the factorial exploratory method of analysis was used, with support from Statistical package software for social sciences (SPSS), version 21. The results show that both innovation in the development and quality have a positive and significant influence over products innovation and in processes developed in SMEs. Furthermore, productsâ€™ quality has a positive and significant influence in the enterprisesâ€™ profitability. Â